2009
DOI: 10.1186/1465-9921-10-87
|View full text |Cite
|
Sign up to set email alerts
|

Truncating and missense BMPR2 mutations differentially affect the severity of heritable pulmonary arterial hypertension

Abstract: BackgroundAutosomal dominant inheritance of germline mutations in the bone morphogenetic protein receptor type 2 (BMPR2) gene are a major risk factor for pulmonary arterial hypertension (PAH). While previous studies demonstrated a difference in severity between BMPR2 mutation carriers and noncarriers, it is likely disease severity is not equal among BMPR2 mutations. We hypothesized that patients with missense BMPR2 mutations have more severe disease than those with truncating mutations.MethodsTesting for BMPR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
4
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 38 publications
6
100
4
6
Order By: Relevance
“…Additional clinical characteristics are of note in the group of patients studied. The first is that the mean age of patients was around 8 yrs younger than the age of patients with IPAH or HPAH in other published series [15,26], although clinical and haemodynamic criteria for inclusion in the study were similar. It is difficult to speculate on the reasons for such a difference, since both the environmental and genetic background were different in these studies, but it shows the severity of the disease occurring in the Chinese Han population, and suggests an increased pressure of geographically and population-specific factors, in conjunction with known genetic factors when BMPR2 mutations are present, or unknown in the case of IPAH.…”
Section: Genetics Of Pulmonary Hypertension D Liu Et Almentioning
confidence: 88%
See 1 more Smart Citation
“…Additional clinical characteristics are of note in the group of patients studied. The first is that the mean age of patients was around 8 yrs younger than the age of patients with IPAH or HPAH in other published series [15,26], although clinical and haemodynamic criteria for inclusion in the study were similar. It is difficult to speculate on the reasons for such a difference, since both the environmental and genetic background were different in these studies, but it shows the severity of the disease occurring in the Chinese Han population, and suggests an increased pressure of geographically and population-specific factors, in conjunction with known genetic factors when BMPR2 mutations are present, or unknown in the case of IPAH.…”
Section: Genetics Of Pulmonary Hypertension D Liu Et Almentioning
confidence: 88%
“…It has been reported that the age at diagnosis is ,10 yrs earlier in PAH patients with mutations than in those without mutations in the BMPR2 gene [15], but in a smaller series of patients, AUSTIN et al [26], found that the younger age at diagnosis in mutation carriers was confined to female patients. In our series of patients, we confirmed that the mean age at diagnosis is ,6 yrs younger in mutation carriers than in noncarriers, but while the relationship was significant in females, there was only a tendency present in males.…”
Section: Genetics Of Pulmonary Hypertension D Liu Et Almentioning
confidence: 93%
“…Genetic mutations in the BMPR2 gene or dysregulated BMPR2 signaling are associated with the development of PVD including pulmonary veno-occlusive disease (PVOD) (89), PAH (90,91), as well as PH associated with COPD and pulmonary fibrosis (PF) (92). Thus, impaired BMPR2 signaling is a unifying feature in the pathogenesis of PVD and the development of PH.…”
Section: Methodsmentioning
confidence: 99%
“…In an international observational study, EVANS et al [13] demonstrated that, in patients with idiopathic, familial and anorexigen-associated PAH, the presence of a BMPR2 mutation is associated with an increased risk of death or lung transplantation. In another study, AUSTIN et al [59] demonstrated the implication of particular BMPR2 mutation types (missense, truncating, large rearrangement or splice defect) in the phenotypic expression of the disease, a result that was not confirmed in the French cohort [60]. Finally, since PAH mostly occurs in females irrespective of BMPR2 mutation status, it has been suggested that oestrogens and oestrogen metabolism might play a role in the pathogenesis of PAH [59,61].…”
Section: Phenotype-genotype Correlationmentioning
confidence: 99%